PEREMPUAN WARANGGANA LANGEN TAYUBDI MASYARAKAT AGRARISAnik Juwariyah Fakultas Bahasa dan Seni, Universitas Negeri Surabaya (Lentera, Jurnal Studi Perempuan, 2013)
Abstract The aim of this writing is to analyze women position who work as waranggana (singer) in Agrarian society. Theory of Social Constructions by Peter L.Berger and Thomas Luckmann is used to analyze this study. The data collection is done by using several techniques such as interview, observation, library research, and recording. The setting of this research is in Nganjuk regency. Nganjuk is one of the Agrarian society whose community keep Langen Tayub alive. Nganjuk also known as a district that has a lot of waranggana. The study shows that female waranggana or taledhek become the core character in langen tayub art. She must keep up appearances, looks attractive and do various movements, including saweran. This action cause female waranggana was mocked up in her daily live. In the Agrarian society waranggana also plays as a mediator between society and danyang desa. Keywords:saweran, erotic dance, agrarian society